Schistosomes in the Lung: Immunobiology and Opportunity - Houlder, Emma L.; Costain, Alice H.; Cook, Peter C.; MacDonald, Andrew S. (Frontiers in Immunology, 2021)
Schistosome infection is a major cause of global morbidity, particularly in sub-Saharan Africa. However, there is no effective vaccine for this major neglected tropical disease, and re-infection routinely occurs following chemotherapeutic treatment. Following invasion through the skin, larval schistosomula enter the circulatory system, migrating to the lung and spending several weeks there before continuing their journey and maturing into adulthood in the mesenteric or urogenital vasculature. Eggs released from adult worms can become trapped in various tissues, with resultant inflammatory responses leading to hepato-splenic, intestinal, or urogenital disease – processes that have been extensively studied in recent years. In contrast, although lung pathology can occur in both the acute and chronic phases of schistosomiasis, the mechanisms underlying pulmonary disease are particularly poorly understood. In chronic infection, egg-mediated fibrosis and vascular destruction can lead to the formation of portosystemic shunts through which eggs can embolise to the lungs, where they can trigger granulomatous disease. Acute schistosomiasis, or Katayama syndrome, which is primarily evident in non-endemic individuals, occurs during pulmonary larval migration, maturation, and initial egg-production, often involving fever and a cough with an accompanying immune cell infiltrate into the lung. Importantly, lung migrating larvae are not just a cause of inflammation and pathology but are a key target for future vaccine design. However, vaccine efforts are hindered by a limited understanding of what constitutes a protective immune response to larvae. In this review, we explore the current understanding of pulmonary immune responses and inflammatory pathology in schistosomiasis, highlighting important unanswered questions and areas for future research.